Makna Afektif dan Kritik Sosial dalam Syair Al-Mutanabbi Menurut Geoffrey Leech: Kajian Semantik - Moza Mutiara Syaqifa; Muhamad Haidar Alfath; Meris Laudy Febrian; Muchammad Naufal Fauqi Adhiya; Akmaliyah (Taqdir, 2025)
Abstract In classical Arabic literature, language serves a dual function, as a medium of aesthetic expression and as a tool for voicing emotion, ideology, and social criticism against the injustices of power, as exemplified in the works of Abu al-Ṭayyib al-Mutanabbī (915–965 CE). This study explores the representation of affective meaning in Al-Mutanabbi’s poems as a form of social critique toward the conditions of society and authority in the 10th century. Geoffrey Leech’s (1981) semantic theory is applied to reveal the emotional and ideological dimensions of his works. Data were collected through documentation and library research, then analysed through identification, classification, and interpretation within the socio-political context. The findings indicate that affective meaning plays a crucial role in conveying the poet’s emotions, such as disappointment, as a subtle medium of criticism. Abstrak Pada sastra Arab klasik, bahasa memiliki fungsi ganda sebagai sarana estetika sekaligus alat untuk menyuarakan emosi, ideologi, serta kritik sosial terhadap ketidakadilan kekuasaan, seperti yang terlihat pada karya Abu al-Ṭayyib al-Mutanabbī (915–965 M). Penelitian ini mengeksplorasi representasi makna afektif dalam syair-syair Al-Mutanabbi sebagai bentuk kritik sosial terhadap kondisi masyarakat dan kekuasaan abad ke-10, dengan menerapkan teori semantik Geoffrey Leech (1981) untuk mengungkap dimensi emosional dan ideologisnya. Pengumpulan data dilakukan melalui teknik dokumentasi dan studi pustaka, dianalisis melalui identifikasi, pengelompokan, serta interpretasi berdasarkan konteks sosial-politik. Temuan menunjukkan makna afektif krusial dalam menyiratkan emosi penyair seperti kekecewaan sebagai medium kritik tersembunyi.